Tingkat Kecemasan Mahasiswa dengan Cabang Olahraga Voli ketika Pertandingan - Mohammad Noval Baghaskara; Aulya Safiyna Nuuril Anwari; Anung Priambodo; Achmad Widodo (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the level of anxiety of volleyball students at Surabaya State University Surabaya State University before competing. This research uses a descriptive. Descriptive quantitative approach with the Sport Anxiety Scale (SAS) questionnaire instrument which includes cognitive, somatic, motor, and affective dimensions. The sample consisted of 17 students aged 19-21 years with 1-8 years of volleyball playing experience. The results showed that the majority of students had a low level of anxiety (88,24%) with an average score of 36,941. Cognitive anxiety was the while somatic and motor anxiety were at low levels. This study underscores the importance of anxiety management through mental training and appropriate coping strategies for the mental training and appropriate coping strategies to improve athlete performance during competition.